Dayak Onion Tuber (Eleutherine Bulbosa (Mill) (Urb) Extract Ethanol Test on The Histopatological Description of Pancreas Wistar Rat Inducted Streptozotocin - Yaturramadhan Harahap, Hasni; Linda Futri, Cory; Aminah, Dalimunthe; Tri, Widyawati (KnE Social Sciences, 2023)
This study aimed to determine the effect of Dayak Union tuber (Eleutherine bulbosa (Mill) Urb) ethanol extract on the regeneration of pancreatic β cells of Wistar rats induced streptozotocin. This research is laboratory experimental study by using 30 rats, they are divided into 5 groups, each group consisting of 6 rats, they are group 1 (normal control), group 2 (sick control) was given Na CMC 1 % b/v, Group 3 (positive control) was given glibenclamide at a dose of 0.25 mg / KgBW, Group 4,5 and 6 were given (Eleutherine bulbosa (Mill) Urb) extract at a dose of 125 mg / KgBB, 250 mg / KgBB and 500 mg / kgBW orally for 15 consecutive days. The histopathological damage level of the pancreas was observed with HE staining using a 400x magnification Olympus Cx-21 microscope. The result of the study showed that there were secondary metabolites of alkaloids, flavonoids, saponins, steroids, and tannins in the ethanol extract of Eleutherine palmifolia (Mill) Urb); The histopathological description showed that the damage to the structure of Langerhans islands and only a dose of 500 mg / KgBB the ethanol extract of Eleutherine palmifolia (Mill) Urb) showed improvement. Keywords: Dayak Onion Tuber; histopathological; extract ethanol